(untitled) (Journal Intellectual Sufism Research (JISR), 2023)
This research aims to determine the effect of istighosah’s solemnity on the level of anxiety in facing life’s problems. This type of research is correlational quantitative. The research was conducted on all students of the Jagad ’Alimussirry Islamic Boarding School, Surabaya. The data were obtained from questionnaires filled out by the research subjects ( self-rating scales ) and then analyzed using quantitative methods to obtain an overview of the level of istighosah and the level of anxiety of students in facing life’s problems. The results showed that there was a significant influence between the level of solemnity in carrying out istighosah experienced by Jagad ’Alimussirry Islamic Boarding School students in facing life’s problems with a significance value of 0.038 <0.05. The average level of concentration of students in carrying out istighosah is moderate and the level of anxiety in facing life is in the mild category. Santri who have a high level of concentration in carrying out istighosah have a high level of anxiety in dealing with light life problems, while students who have a low level of specialization have a high level of anxiety in facing heavy life problems.